Kombinasi Isometric Quadriceps Exercises dan Edukasi Treatment Terhadap Perubahan Nyeri Lutut Pada Penderita Osteoarthritis Genu - Ari Nugrahanta Koesrul; Yohanes Deo Fau; Angria Pradita; Fransisca Xaveria Hargiani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: to find out whats effects give isometric quadriceps exercises and education treatment intervention can reduce knee pain in patient osteoarthritis genu. Methods: This study used the Quasi-Experimental of one group design pre and post group, respondents numbered 20 men and women with purposive sampling techniques, data cellection techniques using NRS test. Normality test using Â Shapiro-Wilk and continued with data analisis using Â WilcoxonResults: in the NRS measurement of isometric quadriceps exercises and education treatment intervention post-test there is a change in decrease of genu pain, and the results of the hypothesis test with normality data distribution show significance value of <0,000Conclusion: Isometric Quadriceps exercises and education treatment have been show to effect reduce knee pain in patient osteoarthritis genu